Enduring Effects: Name Mispronunciation and/or Change in Early School Experiences - Sok, Bonika; Bonnett, Tina (Journal of Teaching and Learning, 2022)
A person’s name(s) is typically tied to their family, culture, and sense of identity. Consequently, when a child’s name is inaccurately pronounced, altered, or avoided, a host of adverse consequences may transpire. Although seemingly innocuous, this necessitates attention, as name mispronunciation and change perpetuate microaggressions ubiquitous for marginalized populations, often in school contexts. In reflection of this, an Intrinsic Case Study, underpinned by a Social Constructivist Philosophical paradigm, was conducted to assemble the experiences of three adults in Ontario, Canada, who had their names mispronounced or changed in early educational experiences. The findings of this research signify that name mispronunciation and modification are pervasive and that teachers are often central contributors to this phenomenon. Moreover, findings denote that discord between one’s identity and cultural self is affiliated with name-orientated microaggressions. Participants of this study beseech teachers to denounce insensitive practices by pledging to accurately pronounce and honour each child’s name and in so doing engender more favourable longitudinal outcomes.